Improving Purchase Decisions Through Trust in The Beauty Business - Nadia Rizky Destiana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Purchasing decisions are important factors in the process of purchasing sustainability, many things must be considered and what factors influence it. Because the purchase decision is the behavior of the customer to continue the purchase or not. This study uses a quantitative approach. The population of this study is the Consumers of the Wijaya Paltinum Beauty Clinic in Pondok Cilegon Indah. This study uses a non-probability sampling technique. From the results of analysis and research explaining related to 1) brand image on purchasing decisions, the Original Sample (O) value is obtained, which is 0.137, the influence of Brand Image on Consumer Purchase Decisions is positive or unidirectional, meaning that the higher the Brand Image, the more it increases Consumer Purchase Decisions. 2) brand image on trust obtained Original Sample (O) value of 0.649 indicating that the direction of influence of Brand Image on Trust is positive or unidirectional, meaning that the higher the Brand Image, the more trust will increase. 3) trust in purchasing decisions from the results of the hypothesis obtained by the Original Sample (O) value of 0.580 indicating that the direction of the influence of Trust on Consumer Purchasing Decisions is positive or unidirectional, meaning that the higher the trust, the higher the Consumer Purchase Decisions.